4(2x+7)-6(4x-8)=12x+3(4x-9)

Simple and best practice solution for 4(2x+7)-6(4x-8)=12x+3(4x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+7)-6(4x-8)=12x+3(4x-9) equation:


Simplifying
4(2x + 7) + -6(4x + -8) = 12x + 3(4x + -9)

Reorder the terms:
4(7 + 2x) + -6(4x + -8) = 12x + 3(4x + -9)
(7 * 4 + 2x * 4) + -6(4x + -8) = 12x + 3(4x + -9)
(28 + 8x) + -6(4x + -8) = 12x + 3(4x + -9)

Reorder the terms:
28 + 8x + -6(-8 + 4x) = 12x + 3(4x + -9)
28 + 8x + (-8 * -6 + 4x * -6) = 12x + 3(4x + -9)
28 + 8x + (48 + -24x) = 12x + 3(4x + -9)

Reorder the terms:
28 + 48 + 8x + -24x = 12x + 3(4x + -9)

Combine like terms: 28 + 48 = 76
76 + 8x + -24x = 12x + 3(4x + -9)

Combine like terms: 8x + -24x = -16x
76 + -16x = 12x + 3(4x + -9)

Reorder the terms:
76 + -16x = 12x + 3(-9 + 4x)
76 + -16x = 12x + (-9 * 3 + 4x * 3)
76 + -16x = 12x + (-27 + 12x)

Reorder the terms:
76 + -16x = -27 + 12x + 12x

Combine like terms: 12x + 12x = 24x
76 + -16x = -27 + 24x

Solving
76 + -16x = -27 + 24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24x' to each side of the equation.
76 + -16x + -24x = -27 + 24x + -24x

Combine like terms: -16x + -24x = -40x
76 + -40x = -27 + 24x + -24x

Combine like terms: 24x + -24x = 0
76 + -40x = -27 + 0
76 + -40x = -27

Add '-76' to each side of the equation.
76 + -76 + -40x = -27 + -76

Combine like terms: 76 + -76 = 0
0 + -40x = -27 + -76
-40x = -27 + -76

Combine like terms: -27 + -76 = -103
-40x = -103

Divide each side by '-40'.
x = 2.575

Simplifying
x = 2.575

See similar equations:

| (-x^2y^3z)(-x^3y^4)= | | (x^2y^4)(xy^7)= | | y-11y= | | 7(-6)+3(-5)= | | (7c^2)(-6c^4)= | | x^4-30x^2-125=0 | | slopey=4x+5 | | 91/4+(-43/3)= | | x^4-30x^2+115= | | s(x+t)=tx-m | | (y^2+4y)-(y^2+10y)= | | (x^2-3xy)-(-2x^2+xy)= | | 2c-8= | | 1-3x=10x-20 | | 4(y+1)-3-5y=2(y-2) | | x+(12-x)=38 | | 4x^3=36 | | -19+8x=x-40 | | (2x^2-4y^2)+(6x^2-2xy+4y^2)= | | 4(y+1)-(3-5y)=2(y-2) | | t^31= | | (3x^2+9x)+(6x-24)= | | 24x^2-11x=0 | | 4(u+4)-7u=-1 | | 7x^2-3x-9=0 | | 32.12*p=3 | | 107+10x=97+15x | | 9x^2-38x+49=0 | | lne^7=y | | u^2-13u+42=0 | | 8-p=-12-13 | | -2x=-3x-2 |

Equations solver categories